A New H4/5 Ordinary Chondrite from North West Saudi Arabia, Al Jawf 001 - Logan Combs; Elizabeth A Gass (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
This research involves the classification and description for the newly discovered ordinary chondrite breccia, Al Jawf 001. Compositional analyses of olivine, pyroxene, and kamacite in each of the major clasts and matrix of the breccia were taken in order to determine its compositional group (H, L, or LL). Percent mean deviations (PMD) of Fe in pyroxenes were calculated for every major clast and matrix, in order to determine the petrologic type of the meteorite. The thermal history was ascertained by pyroxene thermometry and the metallographic cooling rate. The above methods yielded that Al Jawf 001 is an H4/5 chondrite with a peak metamorphic temperature of 750 oC - 850 oC and a cooling rate of 0.1 - 1.0 oC per million years. The high peak metamorphic temperature and slow cooling rate suggest a two-stage cooling-rate history for the H chondrite parent body. Al Jawf 001 provides valuable insight into the history of the H chondrite and adds to the vast amount of information available on ordinary chondrites, increasing our knowledge of the early solar system.